Modernization of Islamic Boarding School Education Institutions According to Azyumardi Azra - Muhamad Nur Zaman; Muhammad Munadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islamic boarding schools have made a significant contribution to efforts to educate the nation's generation. However, in the contemporary era, Islamic boarding schools cannot avoid the influence of modernization, especially with advances in science and technology. Islamic boarding schools are faced with challenges that arise due to changing times and modern life. The ability of Islamic boarding schools to respond to this challenge is a benchmark for the extent to which they can follow the flow of modernization. Azyumardi Azra presents solutions to overcome these problems. For the first issue, he suggested updating management and leadership systems by transforming centralized leadership into collective management. The second problem can be addressed through the contextualization and improvisation of learning methods, even by building new paradigms that adopt emancipatory paradigms. The third problem can be addressed by a similar approach, namely linking the curriculum to the needs of the times. Finally, the fourth problem can be overcome by implementing the legal rule